Transformation of family values of Belarusians in the reflection of the media (the example of the magazine «Rabotnica i sjaljanka») - Artsiomenka-Melyantsova, Alena K. (Journal of the Belarusian State University. Sociology, 2021)
The article examines the change in family values in Belarus as reflected in the materials of the magazine «Rabotnica i sjaljanka» from the 1960s to the 2010s. Based on the analysis of the thematic distribution of publications, the characteristics of the heroines, the female duties declared by the magazine and the presentation of the topic of marriage and family at the level of rhetoric, the following conclusions are drawn. In reflecting the materials of the magazine after the 1990s, the role of family and marriage is increasing, the professional roles and responsibilities of a woman are supplemented by the need to show skill in everyday life, to maintain beauty and attractiveness, which corresponds to the tendencies of traditionalisation of values according to survey data. At the same time, the increase in divorce rates and a decrease in the number of children in the family are normalised.
Keywords: family; marriage; values; gender roles; Belarus; media; transformation